Marketing Strategy for Rattan Crafts in Sungai Baung Village, Rawas Ulu District, North Musi Rawas Regency - Harniatun Iswarini; Puri Pratami Ardina Ningrum; Hafnal Noval Ibrahim (Journal of Global Sustainable Agriculture, 2023)
The purpose of this research was to study the marketing strategy of Pak Udin's rattan crafts in Sungai Baung Village, Rawas Ulu District, North Musi Rawas Regency. The research method used by researchers is a survey method. The sampling method in this study used a saturated sampling method and in this case the determination of respondents was carried out deliberately, namely 1 person Pak Udin as the owner of the rattan handicraft business. This is done with the consideration that the rattan handicraft business owner understands the activities and can provide the information and data needed in connection with research activities. The results showed that  SWOT matrix analysis shows alternative strategies that can be implemented by Mr. Udin's rattan handicraft business, namely: 1) Guaranteeing the quality of product Mr. Udin's rattan handicraft business products and maintaining product sales price stability, 2) Expanding the marketing network, 3) Innovating rattan woven products more uniqly and displays products, 4) Providing training to employees, looking for special workers in the field of marketing.